Expression and prognosis of cellular senescence genes in head and neck squamous cell carcinoma - Chen Feng; Lijuan Zhu; Wei Mao; Pin Dong; Xinwei Chen (Holistic Integrative Oncology)
Abstract Background Cellular senescence refers to cells entering a relatively stable state of cell cycle arrest, which is a barrier that tumor cells must cross to achieve immortalization and plays an extremely important role in preventing the occurrence and development of tumors. In recent years, numerous studies have shown that inducing tumor cells to enter a senescent state has become a feasible tumor control strategy. At present, cellular senescence has become a research hotspot in tumor prevention and treatment, as well as in cell biology. However, the expression and prognostic values of cellular senescence genes in head and neck squamous cell carcinoma (HNSC) remain unclear. Material/Methods We analyzed the expression patterns and prognostic values of cellular senescence genes in HNSC from TCGA and GEO. The TCGA-HNSC data were used as the training group and were divided into high- and low-risk groups, and the GEO database was used as the test group. Analyses included survival analysis, ROC curve analysis, risk curve analysis, independent prognostic analysis and model validation for clinical grouping. We used the HPA database for protein-level validation of the genes. Results We identified 5 cellular senescence genes associated with HNSC, namely, BTG3, EHF, EZH2, TACC3 and TXN. These cellular senescence genes were analyzed in the training and test groups and were found to be significantly associated with the prognosis of HNSC patients. Conclusions The tumor immune microenvironment of HNSC appears to have correlations with certain cellular senescence-related features. Genes associated with cellular senescence, such as BTG3, EHF, EZH2, TACC3, and TXN, show promise as potential diagnostic and prognostic biomarkers for HNSC.